School adoption in teacher education - Markus Janssen (Waxmann Verlag, 2020)
School adoption is an ambitious and innovative partnership model in teacher education which offers unique opportunities for in-service and pre-service teachers. At its core, teachers leave their school to be adopted by teacher students for one week. While the teachers engage in a professional development course outside the school, they are fully substituted by teacher students, who thus have an increased responsibility for the pupils' learning, for the organizational matters of the school and for their own professional development. In this volume, we present different international concepts of school adoption, lessons learned, and first theoretical considerations. With it, we invite teacher educators in schools, universities, and other institutions to engage into a dialogue about the perspectives school adoption offers for teacher education and teacher education research.